Arendt’s Post-dualist Approach to Nature: the Plurality of Animals - Vasterling, Veronica (HannahArendt.net, 2022)
Arendt’s approach to the human-animal distinction shows a clear change from The Human Condition to The Life of the Mind. The two most consequential markers of that change are the concepts of world and plurality. In The Human Condition Arendt tends to distinguish world as the artificial dwelling place of human beings from nature as the realm of living beings. Even though humans and animals are both living beings and creatures of nature, the implication is that making and having a world is what characterizes humans rather than animals. In The Life of the Mind however, Arendt writes that human being and animals are both worldly creatures. With respect to plurality, the change is more evident. Whereas Arendt, in The Human Condition, introduces plurality as one of the human conditions and proceeds to define it as a specifically human achievement, she extends plurality to all living creatures in The Life of the Mind. In this article I will reconstruct Arendt’s reconsideration of the human-animal distinction. I will argue that three themes in The Life of the Mind make the reconsideration of the distinction and the adjustment of the concepts of world and plurality necessary, namely the deconstruction of metaphysical fallacies, the introduction of a phenomenological ontology and the influence of Portmann’s phenomenology of animals. With this reconstruction I want to join the growing reception of Arendt as a thinker who offers important resources to ecological thought, in this case, with original reflections on resemblances and distinctions of humans and animals.